The algorithm and the almighty: rethinking omniscience, suffering, and salvation - Madero, Kimberly A. (Religious studies, 2025)
This article examines the philosophical and theological implications of artificial intelligence (AI) and the technological singularity for core religious concepts. The predictive capacities of AI challenge traditional accounts of divine omniscience, raising critical questions about the distinction between algorithmic foreknowledge and theological models of perfect knowledge. The increasing determinacy of human behaviour through data-driven systems complicates classical formulations of human freedom and moral responsibility. Additionally, the potential for artificial suffering demands an expansion of theodicy and a reassessment of the creator-creature relationship in light of human technological agency. Finally, emerging technological eschatologies, promising digital immortality and transcendence, confront religious soteriology with novel anthropocentric models of salvation.This study argues that the philosophy of religion must critically rearticulate its categories of knowledge, suffering, and eschatological hope to remain conceptually viable in a world mediated by intelligent systems.